Effective and Efficient Herbst Appliance Therapy for Skeletal Class II Malocclusion Patient with a Low Degree of Collaboration with the Orthodontic Treatment - Bernardo Quiroga Souki; Barbra Duque Costa Bastos; Luana Fialho Ferro Araujo; Wagner Fernando Moyses-Braga; Mariele Garcia Pantuzo; Paula Loureiro Cheib (Case Reports in Dentistry)
The current concept for effective and efficient treatment of skeletal Class II malocclusion prescribes that interceptive approach should be delivered during the pubertal growth stage. However, psychosocial issues and a greater risk of dental trauma are also factors that should be addressed when considering early Class II therapy. This paper reports a case of a patient that sought orthodontic treatment due to aesthetic discomfort with the incisors’ protrusion. Two previous treatments failed because patient’s collaboration with removable appliances was inadequate. Given his history of no collaboration and because the patient was in the prepubertal stage, it was decided to try a different approach in the third attempt of treatment. Traumatic injury protective devices were used during the prepubertal stage and followed by Herbst appliance and fixed multibrackets therapy during the pubertal stage, resulting in an adequate outcome and long-term stability.